An Information‐Based Theory of Time‐Varying Liquidity - DALEY, BRENDAN; GREEN, BRETT (Journal of Finance, 2016)
ABSTRACT We propose an information‐based theory to explain time variation in liquidity and link it to a variety of patterns in asset markets. In “normal times,” the market is fully liquid and gains from trade are realized immediately. However, the equilibrium also involves periods during which liquidity “dries up,” which leads to endogenous liquidation costs. Traders correctly anticipate such costs, which reduces their willingness to pay. This foresight leads to a novel feedback effect between prices and market liquidity, which are jointly determined in equilibrium. The model also predicts that contagious sell‐offs can occur after sufficiently bad news.